La trascendencia constitucional de la neutralidad de red - Fernández Baca, Dilmar Villena (2016)
New technologies have transformed the traditional ways in which people develop and express themselves. In that context, the internet has meant a revolution in different spheres of society, in which the users and network providers are developed. Faced with this, the question arises: Should the relations that are presented in the network be regulated?.In this article, the author develops the principle of net neutrality as the basis of the protection of the fundamental rights from the different agents that are related by this means. It will be exposed the current regulation of the matter and its scope, which finds its support in the constitutional regulation.